Record fragmentation due to transfusion at multiple health care facilities: a risk factor for delayed hemolytic transfusion reactions. Issue 1 (27th May 2013) - Unni, Nisha; Peddinghaus, Marie; Tormey, Christopher A.; Stack, Gary
<x xml:space="preserve">Abstract</x> Background Patients transfused at more than one health care facility face safety risks, because their transfusion record is fragmented. Blood group antibodies documented at one facility may be unknown to others. Because many antibodies are evanescent, access to prior antibody records is important for preventing incompatible transfusions and delayed hemolytic reactions. The study goal was to quantify multisite transfusion activity and its impact on antibody record accuracy. Study Design and Methods Patients (n = 100) undergoing hospital transfusion testing were surveyed to determine the locations and dates of any prior transfusions. Also, transfusion records were examined to determine whether patients (n = 200) known to be alloimmunized at one hospital had antibody testing done at another nearby hospital and, if so, how often the results were discrepant. Results Twenty‐three percent (23/100) of patients undergoing type‐and‐screen testing reported receiving transfusions at 24 other facilities. Locations of transfusions that occurred elsewhere were 54.2% (13/24) at eight other in‐state hospitals, 12.5% in bordering states, 20.8% in more distant states, and 12.5% during military service. Twenty‐one percent (42/200) of patients known to be alloimmunized at one hospital had antibody test results on record at another nearby hospital. Antibody discrepancies were noted in 64.3% (27/42) of cases. The most common discrepancy was the failure of one facility to detect an antibody. Conclusion Multisite transfusions were common. For patients seen at both of two nearby hospitals, antibody records were frequently discrepant. The findings support the need for interfacility sharing of transfusion records, particularly at the regional level.